Work Boundary Management Tactics and Work-Family Conflict Among Offshore Employees in the Oil and Gas Industry - Nurfitri Nadzirah, Sarkawi; Nur Fatihah, Abdullah Bandar; Zaiton, Hassan; Sheilla Lim, Omar Lim; Heng, Chin Siong (UNIMAS Publisher, 2024)
Managing work-family conflict is crucial for offshore employees in the oil and gas industry, where the boundaries between work and family can blur due to extended offshore assignments. This study examines the relationship between various work boundary management tactics, including behavioural, physical, communicative, temporal, and work-family conflict among offshore employees. A total of 95 offshore employees from selected oil and gas companies participated in the study. Pearson's correlation analysis was used to assess the relationships between boundary management tactics and work-family conflict. The results indicate significant relationships between behavioural, physical, and communicative tactics and work-family conflict, while temporal tactics were associated with positive but weak and non-significant relationships. These findings offer actionable insights for enhancing work-life balance policies tailored to offshore settings and suggest directions for future research in this area.